Suitability of Kitchen Waste Water in Agriculture - Mini Abraham; Kurien E. K; Bhindhu P. S; Gilsha Bai E. B. (International Journal of Economic Plants)
Water has become a scarce input in agriculture. Reuse of household waste water is helpful in solving water scarcity problems in household agriculture during summer months.  Reuse of waste water for garden irrigation should be encouraged in urban and rural households. A study was conducted during the year 2016-2017 at Agronomic Research Station, Chalakudy to assess the water quality of household waste water for reuse in agriculture.  Samples were collected from households of different localities and laboratory analysis was conducted to assess different quality parameters.  Physio-chemical parameters such as pH, EC, chloride, carbonates, bicarbonates, sodium, potassium, boron, calcium, magnesium, SAR and RSC were analyzed. It was found that all the parameters tested were within the safe limits and water is moderately suitable or suitable for irrigation. Presence of heavy metal such as lead, chromium and nickel was analyzed and found within the permissible limits in kitchen waste water.  Observation on quality parameters of kitchen waste water showed that EC, SAR and boron were low, but RSC ranged from low to medium level. In continuation, a further field trial on okra (var. Arka anamika) was conducted using kitchen waste water during the summer season in the year 2016–17. Performance of the crop was compared with the crop irrigated using normal well water. Yield of the crop irrigated using kitchen waste water was 6.20 kg plot-1 while it was only 4.10 kg plot-1 with normal well water. Household kitchen waste water is a very good source of water for irrigating homesteads.